The influence of He-Ne Laser (632.8 nm) on Candida albicans isolated from complete upper dentures: In vitro study (Baghdad Science Journal, 2025)
The main objective of this study is to determine whether the use of He-Ne Laser (632.8 nm wavelength and power 0.5 mW) is an eligible and effective tool to kill or reduce the cell viability of Candida albicans isolated from complete upper dentures.Twenty one swabs were taken from the complete upper dentures. Only six swabs showed positive cultures for C. albicans.The isolate was divided into two groups, group I was not irradiated (control), and group II was irradiated by He-Ne Laser for different periods (10, 15, 20, and 30) min.After irradiation, the results showed a significant reduction in the viable cell count and colonies diameters especially at exposure periods 10 and 15 min.Although the low power He-Ne Laser was not eradicating the cell itself, but it affected on the viable cell count and colonies diameters comparing with the control.